The First Case of Foot-and-Mouth Disease Caused by O/ME-SA/IND-2001 Virus in Kazakhstan - A. K. Nakhanov; Kh. B. Abeuov; Z. D. Omarova; T. T. Ermekbai; E. D. Burashev; M. B. Orynbayev (Проблемы особо опасных инфекций, 2023)
In Kazakhstan, foot-and-mouth disease (FMD) outbreaks were recorded in 2011–2013 in the southern and eastern regions where FMD vaccination is in place. In January 2022, in Kiikty village of the Shetsky district, Karaganda Region, Republic of Kazakhstan, cases among cattle clinically similar to foot-and-mouth disease were reported. The aim of the research was to establish the cause of the disease and to perform the typing of the pathogen. Materials and methods. Samples from sick animals were tested using PCR, sequenced and typed in compliance with the protocol developed by the International Office for Epizootic Diseases (OIE). Results and discussion. A cytopathogenic agent has been isolated from the BHK-21 cell culture, identified through real-time RT-PCR and electron microscopically as FMD virus. Molecular genetic studies have revealed that the infection of cattle in the Karaganda Region was caused by the FMD virus circulating in the territory of the countries bordering Kazakhstan (China, Russia, Mongolia) and belonging to type O, topotype ME-SA, genetic line Ind-2001. FMD virus isolated in Kazakhstan is genetically related to the FMD line from Asia and is a new FMDV genotype for Kazakhstan, assigned to the ME-SA topotype of the Ind-2001 genetic line. This study once again proves the need for continuous genetic typing of FMD viruses to improve the effectiveness of preventive measures.